¿DIOS SE HA PUESTO REALMENTE DE MODA? - VALENZUELA, EDUARDO (Humanitas (07172168))
The article analyzes the current situation of religion, focusing on the apparent "God trend" and the debate about a possible religious revival. Although some data suggest a slight increase in religious interest, especially in the United States after the pandemic, surveys show that secularization continues in Europe and has stabilized in North America, mainly due to generational turnover and the difficulty of transmitting faith to young people. In Latin America, except for Chile, a religious reconfiguration towards evangelical and Pentecostal churches predominates rather than massive secularization. Various hypotheses about the future of religion are presented, ranging from its progressive decline to post-secularization, which acknowledges the persistent social relevance of religion, albeit with less influence and fewer believers.